0986 Tasimelteon Improves Symptoms of Major Depression in an African American Population. (27th April 2018) - Polymeropoulos, M; Xiao, C; Polymeropoulos, C
Abstract: Introduction: Major Depressive Disorder (MDD) is often associated with insomnia and it has been hypothesized that circadian rhythm disruption may be involved in the etiology of MDD. We have conducted a large clinical study evaluating the effects of the circadian regulator tasimelteon on depressive symptoms in patients with MDD. Methods: 507 patients with MDD were enrolled in a double masked placebo controlled study randomized on either tasimelteon 20 mg (n=254) or placebo (n=253). Patients were assessed at baseline and weekly for 8 weeks on a number of depression scales including the Hamilton Depression Scale (HAMD). Results: Tasimelteon and placebo treated patients appeared to improve similarly from baseline by 8.1 and 7.8 points respectively on the HAMD scale (pvalue =0.57). An analysis by race however revealed a significantly positive effect of tasimelteon among African American patients. Out of 507 randomized patients 166 (32.7%) were African American (AA) of which 78 were treated with tasimelteon and 88 with placebo. At 8 weeks African American MDD patients treated with tasimelteon improved by 9.9 points on the HAMD scale as compared to 6.9 points for the placebo treated patients (pvalue =0.018). In a responder analysis (improvement in the HAMD scale of 50% or greater from baseline) 59% of tasimelteon treated patients improved as compared to 30% of placebo treated patients (pvalue =0.0019). Conclusion: Tasimelteon 20 mg was shown to improve symptoms of depression in African American patients with MDD in a meta-analysis of a large MDD clinical study which may suggest a circadian component in the etiology and treatment of Major Depression. Support (If Any): This work was supported by Vanda Pharmaceuticals Inc.